2019
DOI: 10.1177/0301574219878947
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Reinforced Oral Hygiene Instruction Program With and Without Professional Tooth Cleaning on Plaque Control and Gingival Health of Orthodontic Patients Wearing Multibracket Appliances

Abstract: Introduction: Fixed orthodontic therapy is considered to be one of the important risk factor for plaque accumulation, since various orthodontic components serves as the retentive areas for plaque accumulation and thus increasing the risk of caries and periodontitis. Therefore these patients must be encouraged to maintain good oral health throughout the treatment. Objective: To investigate the effects of reinforced oral hygiene instruction programme with and without professional tooth cleaning on the plaque ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…Poor plaque control is a key determinant of periodontal disease [ 126 ]. Effective OHI can control and reduce plaque accumulation and improve the gingival health status, independent of professional prophylactic care [ 127 , 128 ]. Supporting this evidence, our findings indicated that probiotic supplementation combined with OHI resulted in statistically significant improvements in all clinical outcomes, including plaque accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…Poor plaque control is a key determinant of periodontal disease [ 126 ]. Effective OHI can control and reduce plaque accumulation and improve the gingival health status, independent of professional prophylactic care [ 127 , 128 ]. Supporting this evidence, our findings indicated that probiotic supplementation combined with OHI resulted in statistically significant improvements in all clinical outcomes, including plaque accumulation.…”
Section: Discussionmentioning
confidence: 99%
“…A study that examined the effect of a reinforced oral hygiene instruction program on the gingiva health of patients using fixed orthodontic appliances, conducted by Singla et al (2019), demonstrated that there was an improvement in the subjects' psychomotor ability to clean the oral cavity, as indicated by a significant decrease in the mean plaque score (PI) and gingival index (GI) in the test group after four and eight weeks of using the program [47]. In addition, Williams et al (2018) conducted a study that compared the effectiveness of oral hygiene instructions provided through verbal instructions and the use of computer assistance, in which a lower plaque score was obtained in the group that was given the intervention of computer-assisted oral cleaning instructions, although it was only significant in subjects aged 50 years and under, compared to the group that was only offered verbal instructions by professionals [48].…”
Section: Discussionmentioning
confidence: 99%
“…The risk of inflammation in pregnant women with orthodontic appliances is also caused by high OHI-S. Orthodontic appliance use can also increase plaque formation, which may impact the health of the gingiva and periodontium [ 37 ]. Oral hygiene is important to maintain and even increase, especially in pregnant women with orthodontic appliances, in order to prevent caries, gingivitis, and periodontitis.…”
Section: Discussionmentioning
confidence: 99%